INFLUENCE OF SOIL PHYSICAL PROPERTIES ON SOIL LOSS DUE TO YAM HARVESTED ON A SANDY LOAM SOIL IN IWO, OSUN STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Soil loss due to crop harvesting (SLCH) has been established as an important soil erosion process that has contributed to soil degradation in many countries of the world. However, the quantification of SLCH, particularly concerning yam tubers, remains unstudied globally, despite yam being a crucial staple food in Nigeria. This research examines how soil physical properties affect soil loss during yam harvesting on sandy loam soil in Iwo, Osun State, Nigeria. Manual harvesting of yam tubers was conducted, measuring both their weight and the soil attached to them. The study analyzed the impact of soil properties such as aggregate stability, available water content, bulk density, and texture on soil loss. Results indicated sand content (671.00 g/kg), a bulk density of 1.30 g/cm³, saturated hydraulic conductivity of 7.37 cm/hr, and a moisture content of 15.70%. The infiltration rate averaged 12.5 units in 11 minutes. Manual mound tillage produced the highest soil loss (160.00 kg/ha/harvest), while Zai pit tillage resulted in the least (75.60 kg/ha/harvest). The study highlights the importance of adopting effective soil conservation practices and suggests developing yam harvesters that replicate the hand rubbing technique to reduce soil loss.
Keywords: Soil physical properties; Soil loss; Yam harvesting; Sandy loam soil; Tillage practices